2001
DOI: 10.1007/pl00002919
|View full text |Cite
|
Sign up to set email alerts
|

QTL analysis of agronomic traits in barley based on the doubled haploid progeny of two elite North American varieties representing different germplasm groups

Abstract: A better understanding of the genetics of complex traits, such as yield, may be achieved by using molecular tools. This study was conducted to estimate the number, genome location, effect and allele phase of QTLs determining agronomic traits in the two North American malting barley (Hordeum vulgare L.) quality variety standards. Using a doubled haploid population of 140 lines from the cross of two-rowed Harrington×six-rowed Morex, agronomic phenotypic data sets from nine environments, and a 107-marker linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
61
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 27 publications
10
61
1
2
Order By: Relevance
“…GWT was controlled predominantly by vrs1 and uzu as detected previously 3,5,15,23 . The allele of Azumamugi at the vrs1 locus increased GWT by 9.15-11.75 g ( Table 4).…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…GWT was controlled predominantly by vrs1 and uzu as detected previously 3,5,15,23 . The allele of Azumamugi at the vrs1 locus increased GWT by 9.15-11.75 g ( Table 4).…”
Section: Resultssupporting
confidence: 67%
“…A LOD score threshold of 3.0 was used to identify QTLs. The position of detected QTLs were compared with the ones of former QTL studies 1,3,10,15 consulting integrated maps 6,16 .…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, their plant height QTL is bordered by alm locus, which is placed in 3H-Bin 3 (next to btr1 locus) http://wheat.pw.usda.gov/ cgi-bin/graingenes/report.cgi?class=marker&name=alm and by the marker FGX OWB00380, which corresponds to marker 12 31017 located at 56.40 cM on 3H . Another study on barley plant height identified QTL on chromosome 3H at 67-78 cM (Marquez-Cedillo et al, 2001). Comparison of QTL flanking markers, from Marquez-Cedillo et al study and our study, in barley integrated genetic maps at the GrainGenes website (http://wheat.pw.usda.gov) suggested that our QTL was in a different genetic location than the QTL from Marquez-Cedillo et al study.…”
Section: Discussionsupporting
confidence: 39%
“…It was found that some flag leaf traits, such as length, width and angle, were inherited quantitatively (Yang and Lu, 1991 Meanwhile, quantitative trait loci (QTL) mapping provides a powerful tool to study complex traits at the molecular level, and considerable progress has been made in the genetic research on yield, yield components, and malting quality traits in barley (Backes et al, 1995;Baum et al, 2003;Bezant et al, 1997;Kjaer and Jensen, 1996;Li J.Z. et al, 2005;Marquez-Cedillo et al, 2001;Mather et al, 1997;Sameri et al, 2006;Thomas et al, 1995;Yin et al, 1999). However, little research has been done in understanding of genetic mechanisms for flag leaf traits in barley.…”
Section: Introductionmentioning
confidence: 99%